Protección de Datos Personales en el Marco de la COVID-19: el Caso de CoronApp en Colombia - Cabrera, Karen; Montenegro, Yamile (Law, State and Telecommunications Review, 2022)
[Purpose] Identify the shortcomings that politics present in the processing of CoronApp data, in contrast to the internal regulations that protect the handling of personal data in Colombia [Methodology/Approach/Design] The research is of a qualitative work where, through the file review, are analyzed the normative documents of the protection of personal data in Colombia in contrast with the data processing policies of the CoronApp application. [Findings] This work concluded that it is necessary to know the handling that is giving to the data so far, to verify if it is feasible to continue using it and, if so, restructure those policies so that it complies with the legal requirements. [Practical implications] This article provides evidence about the shortcomings that the CoronApp application presents about handling personal data and the consequences of their lack of protection. In that sense modification the normative according to the internal regulations is urging, since could cause damages to the holders of those rights. In addition, the article presents some recommendations on how these modifications have to be presents. [Originality] CoronApp application has been recently implemented in Colombia, as a technological solution to collaborate in the management and containment of the COVID-19 virus, is nourished by a series of data that needs to be protected. However, few are the studies that show whether it complies with the legal requirements to protect personal data and which could be the consequences of lack of protection.